Fatal rupture of pulmonary artery pseudoaneurysm after thoracic radiation therapy against lung squamous cell carcinoma: A case report and literature review. Issue 2 (7th December 2020) - Fukuda, Yosuke; Homma, Tetsuya; Uno, Tomoki; Murata, Yasunori; Suzuki, Shintaro; Shiozawa, Eisuke; Takimoto, Masafumi; Sagara, Hironori
Abstract: Pulmonary artery pseudoaneurysm is a rare but fatal condition. It has been associated with lung cancer, abscesses, and radiation therapy. Identification in patients with hemoptysis is critical, and timely interventional therapy is warranted. Abstract : Pulmonary artery pseudoaneurysm is a rare but fatal condition. It has been associated with lung cancer, abscesses, and radiation therapy. Identification in patients with hemoptysis is critical, and timely interventional therapy is warranted.